Pola Komunikasi Pelatih Dalam Memotivasi Berlatih Atlet Perguruan Pencak Silat Satria Muda Indonesia Komisariat Wilayah Kabupaten Bekasi - Teguh Saputro; Murtiadi; Roynaldi Arista (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Pencak Silat is an Indonesian cultural heritage that not only teaches martial arts techniques but also instills moral values, ethics, and discipline. In the athlete development process, coaches play a significant role, particularly in fostering training motivation through the communication patterns they implement. This study aims to examine the coach's communication patterns in motivating athletes at the Satria Muda Indonesia Pencak Silat School, Bekasi Regional Commissariat. This research employs a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentation. The informants consist of the head coach and two senior athletes. The data were analyzed using the interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the coach applies one-way, two-way, and multi-directional communication patterns, adjusted according to the athlete’s age and character. Both verbal and non-verbal communication are used effectively, supported by emotional approaches and informal social activities. This communication strategy fosters strong emotional bonds and a positive training environment. Effective communication has been proven to increase athlete motivation, discipline, and enthusiasm during the training process.